Implementasi Manajemen Pendidikan Karakter Dalam Mengembangkan Minat, Sikap Dan Perilaku Positif Siswa di Madrasah Aliyah Laboratorium Kecamatan Telanaipura Kota Jambi Tahun Pelajaran 2023/2024 - Andika Andika (Student Research Journal, 2024)
Islamic education is a conscious, planned effort in preparing students to know, understand, live up to the process of believing in Islamic teachings in their lives, or it can be said that it is an attempt to change individual behavior in their personal lives, social life and the surrounding natural life through educational process that is based on Islamic values so that later students are able, able and skilled in carrying out life as an effort to maintain their survival and development. For this reason, in writing this thesis, the type of research used by the author is a qualitative descriptive research method, emphasizing the power of direct field observation and then analyzing data from existing data sources. And the results of this study indicate that Islamic education and life skills are a component that cannot be separated, because both are a unified whole in relation to life. This research also shows that the concept of life skills can be used as a new direction in Islamic education, by integrating several aspects of life skills with Islamic education. From the results of this study it can be concluded that the application of life skills can provide abilities, abilities and skills to students both in the fields of information technology and religion. As a provision to live their lives, it is hoped that each student will have personal, rational, social, academic and vocational skills that are integrated in Islamic education. The results of this study are expected to be used as a constructive vehicle in relation to improving the quality of Islamic education in the future, both theoretically and practically, besides that the results of this research cannot be said to be final, therefore it is hoped that there will be further researchers who review the results of this study.